FOSTERING COMPETENCE AND PERSON-JOB FIT IN AN EFFORT TO IMPROVE EMPLOYEE PERFORMANCE (International Journal of Innovative Technologies in Economy, 2025)
Employee performance plays a vital role in helping organisations reach their goals successfully. Enhancing competencies and aligning individual traits with job requirements can lead to improvements in performance. The primary aim of this study is to explore the correlation between skills and alignment with job responsibilities in order to improve the performance of workers at the Cirebon Branch Office of Perum Bulog. A survey involving 91 employees was conducted for this study, using a quantitative research approach. The sampling technique used was saturated sampling. Information was gathered by utilising a Likert scale questionnaire and then examined using multiple linear regression through SPSS software version 25. The study indicated that exceptional proficiency in one's role is critically important for enhancing employee performance. When individuals possess robust skills, they are more likely to execute their responsibilities effectively and meet the expectations set before them. Furthermore, a strong alignment between an individual and their position significantly contributes to improved performance outcomes. The fit between individuals and jobs increases motivation, job satisfaction, and effectiveness in completing tasks. The implications of these results indicate the need for companies to integrate human resource development strategies through training, proper job placement, and recruitment that consider the fit between individuals and jobs.